2015
DOI: 10.1115/1.4031363
|View full text |Cite
|
Sign up to set email alerts
|

A Geometric Model for the Coiling of an Elastic Rod Deployed Onto a Moving Substrate

Abstract: We report results from a systematic numerical investigation of the nonlinear patterns that emerge when a slender elastic rod is deployed onto a moving substrate; a system also known as the elastic sewing machine (ESM). The discrete elastic rods (DER) method is employed to quantitatively characterize the coiling patterns, and a comprehensive classification scheme is introduced based on their Fourier spectrum. Our analysis yields physical insight on both the length scales excited by the ESM, as well as the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…All the aforementioned patterns and their order of appearance are consistent with what is observed in both viscous and elastic cases [19][20][21]. This robustness suggests the existence of a common explanation for the formation of these patterns, which was recently given in [18,21] and is detailed in the following section so that it may be adapted to molten glass.…”
Section: (B) the Patternssupporting
confidence: 84%
See 1 more Smart Citation
“…All the aforementioned patterns and their order of appearance are consistent with what is observed in both viscous and elastic cases [19][20][21]. This robustness suggests the existence of a common explanation for the formation of these patterns, which was recently given in [18,21] and is detailed in the following section so that it may be adapted to molten glass.…”
Section: (B) the Patternssupporting
confidence: 84%
“…Embedded in geometry, coiling patterns are indeed found to be generic: they resist changes in the intrinsic mechanical properties of the thread. In particular, similar patterns have been observed when the thread is elastic [19][20][21]. Here, we illustrate how such fluidic instabilities may be applied to further the capabilities of additive manufacturing.…”
Section: Introductionsupporting
confidence: 69%
“…The coiling behavior of the electrospun micro/nanofiber is similar to the gravity driven rope coiling, although their characteristic lengths are micro/nanoscale and centimeters/millimeters, respectively. Recently, Brun et al [ 37 , 38 ] developed a quasi-static geometrical model (GM) to capture the various buckling patterns of thin viscous jet or elastic rope, and successfully calculated the bifurcation threshold of different patterns. They found that the jet/collector velocity match coefficient was the key factor for pattern variation, and this was coincidence with the HE-printing results.…”
Section: Resultsmentioning
confidence: 99%
“…In the geometrical model [ 37 , 38 ], the deposited trace on collector, namely the patterns of meander, alternating loops, translated coiling, etc. is a combination of the orbit of the contact point (regular coiling when collector is motionless) and the movement of the collector.…”
Section: Resultsmentioning
confidence: 99%
“…Higher voltage or smaller nozzle-to-collector distance correspond to stronger electrical filed, thus a larger falling speed and a smaller jet diameter can be achieved due to the more severe electrical stretching. Large falling speed indicates that large collector velocity is needed to stretch the jet from curve to straight (as shown in Figure 2 d) [ 30 , 31 , 32 ]. Small jet diameter corresponds to small bending/torsional stiffness, thus small buckled patterns deposited on collector [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%